Elevated urine albumin-to-creatinine ratio as a risk factor for cognitive impairment in older adults: A cross-sectional analysis of NHANES data - Yubo Teng; Jingyi Zhang; Boxiang Yang; Qin Luo; Yu Xue; Miao Zhang (PLoS ONE, 2025)
Background Cognitive impairment is an escalating challenge in aging populations, with risk factors extending beyond traditional domains. The urine albumin-to-creatinine ratio (UACR), a marker of kidney and vascular health, has been associated with systemic dysfunction, yet its association with cognitive impairment remains underexplored. This study aims to delve into the association between UACR and cognitive function in older adults. Methods This study conducted a cross-sectional analysis using data from the 2011–2014 National Health and Nutrition Examination Survey (NHANES), including 2,385 adults aged ≥60 years. Cognitive function was assessed using composite ‘Cognitive Scores’ derived from standardized tests. Participants were categorized into quartiles based on UACR levels. Multivariate linear regression models were used to evaluate the association between UACR and cognitive scores. Additionally, multivariate logistic regression models were used to assess the relationship between UACR and cognitive impairment, adjusting for demographic and clinical covariates. Smooth curve fitting and interaction analyses were also performed to further investigate the relationship between UACR and cognitive impairment. Results For every 10-unit increase in UACR, cognitive scores declined by 0.019 (β = -0.019, 95% CI: -0.036 to -0.002; P < 0.05), and the odds of cognitive impairment increased by 2.6% (OR = 1.026, 95% CI: 1.004 to 1.048; P < 0.05). This trend was also observed in participants with UACR levels below 30, where for every 10-unit increase in UACR, cognitive scores decreased by 0.013 (β = -0.013, 95% CI: -0.027 to -0.001; P < 0.05), and the odds of cognitive impairment increased by 1.4% (OR = 1.014, 95% CI: 1.003 to 1.038; P < 0.05). The study also identified a nonlinear relationship, where the risk of cognitive impairment increased with rising UACR levels, but this risk plateaued at a UACR value of 12.86. Hypertension was found to be a significant factor influencing the relationship between UACR and cognitive impairment (P for interaction < 0.05). Conclusion This study highlights the significant association between elevated UACR and cognitive impairment in older adults. Notably, even at lower UACR levels, increases in UACR are associated with a higher risk of cognitive impairment. These findings underscore the importance of incorporating kidney health management into strategies aimed at preventing cognitive decline. Further longitudinal studies are needed to clarify the causal relationship and explore interventions targeting UACR to preserve cognitive function.